Consequences and management of symptoms of menstrual cycle and association with a healthy lifestyle among educated females in Tangail region of Bangladesh: a cross sectional study - Ira, Israt Jahan; Arefin, Sayema; Eva, Effat Jahan; Tinu, Shafayatun Nahar (International Journal Of Community Medicine And Public Health, 2021)
Background: Menstrual cycle is a normal physiological incident in the life of a girl. Often it is not properly understanded or realised that, maintaining a proper hygiene and the symptom management play a vital role in leading a healthy life for a woman. The condition is even worse in developing countries. The aim of the study is to assay the effects, pattern of the cycle and symptom management among the educated female populations in Tangail region in Bangladesh. Methods: A cross sectional study was conducted in Tangail with 305 participants. Data collection took place from October,2020 to December, 2020 following a structured questionnaire. The data obtained were analysed through SPSS 23.0 version. Results: Among the study population 61.5% were in the age range from 20-30 years. Most of the participants have done their post graduation (42.4%). The daily water intake is really important for a good menstrual cycle. 40.8% of the female take less than 2 litres of water which is alarming. 78.3% having their cycle regular with 68.8% of normal flow. 70.4% having their cycle for 3-5 days which is okay. 53.6% of the participants faces Premenstrual syndrome for which 12.2% take medications and 18.8% participants take medicine during menstruation. The study demonstrates a statistically significant association between the age and PMS as well as between the life stress of a women and PMS. Conclusions: The study’s goal is to look into the effects and management of menstruation, as well as the demographic and lifestyle characteristics of the participants. To ensure female’s health, menstrual cycles must be maintained properly.